Intravenous cephalosporin versus non-cephalosporin-based prophylaxis to prevent surgical site infections in colorectal surgery patients: A systematic review and meta-analysis - Bowder, Alexis N. (Ann Med Surg (Lond), 2021)
BACKGROUND: Surgical site infection (SSI) is common in colorectal surgery patients and associated with morbidity and mortality. Guidelines recommend preoperative intravenous antimicrobial prophylaxis with aerobic and anaerobic coverage to reduce SSI risk. Cephalosporin based prophylaxis (CBP) regimens are recommended as first-line prophylaxis, and non-cephalosporin based are recommended as alternative prophylaxis (AP). We evaluate the efficacy of CBP versus AP in preventing surgical site infections in colorectal surgery patients. METHODS: A systematic review and meta-analysis was conducted of studies published between 2005 and 2020 in MEDLINE and Web of Science. Studies were excluded if intravenous antimicrobial prophylaxis was not administered, or if oral and intravenous prophylaxis were routinely co-administered. Heterogeneity was reported using the Q-statistic and I(2)-statistic. Publication bias was evaluated using a funnel plot and Egger test for small study effects. Statistical significance was defined as a two-sided p < 0.05. RESULTS: 11 studies met inclusion criteria. AP was not associated with increased SSI risk at 30 days compared to CBP (OR 1.01, 95% CI 0.91, 1.13; OR < 1 favors AP). There was no effect size variability in subgroup analysis comparing higher-to lower-quality studies (I(2) = 99%, P = 0.17). Subgroup analysis by publication year approached a significant difference in effect size between studies published prior to 2014 and later than 2014 (I(2) = 99%, P = 0.06). CONCLUSIONS: Meta-analysis of 11 studies of SSI risk in adult colorectal surgery patients suggest that SSI risk is similar for patients receiving CBP or AP, subgroup analysis of studies published since 2014 suggest increased SSI risk with AP compared to CBP.